Algérie — Une histoire de haine et d’amour - Szuhaj, Katalin (Verbum – Analecta Neolatina, 2008)
The paper examines the French-Algerian relationship through the subjects of immigration and emigration. This historical analysis focuses on 20th-century Algerian emigration with a special regard to the great wave of emigration that followed the Algerian war (1954-1962). The first part of the article presents contemporary Algerian industry, culture and social life. The multifaceted picture of 21st-century Algeria raises further issues. I try to find answers by giving a historical overview. The second part focuses on France and the life of different generations of Algerian immigrants in the country. I will consider the Parisian example that opened the wave of change of social life into intercultural society. The main objective of this article is to encourage the revaluation of the antagonistic political relationship between Algeria and France and to offer a new possibility to overcome the hostility caused by the recollection of the war.